Plum spooky - Evanovich, Janet (Evanovich, Janet. Stephanie Plum novel., 2009)
Wulf Grimoire is a world wanderer and an opportunist who can kill without remorse and disappear like smoke. He's chosen Martin Munch, boy genius, as his new business partner, and he's chosen the Barrens of Trenton, New Jersey, as his new playground. It's up to Plum and Diesel, an über bounty hunter with special skills when it comes to tracking men and pleasing women, to hunt down Munch and Grimoire.